Women Empowerment as a Component of Social Responsibility in Participatory Varietal Selection - Parvaze A Sofi (Journal of Krishi Vigyan, 2015)
Rural women are key agents for achieving the transformation in terms of economic, environmental and social changes required for sustainable development. However, in developing countries women face a multitude of problems which an otherwise gender blind approach often fails to appreciate or even identify. The unpredictable social, political, economical and personal hardships they face daily are difficult to grasp. The participatory approaches find relevance in a way that they give appropriate weightage to gender differences and recognize the fact that needs of men and women are invariably different. The varietal development process also needs to be integrated into a holistic programme instead a compartmentalised activity where plant scientists, farming system experts, economists, extension persons, farmers and consumers are equally conscious to and contribute through their capacities towards development of varieties that meet the aspirations of small holder farmers in terms of productivity enhancement and livelihood security